PENGARUH KESADARAN, SANKSI PERPAJAKAN, TINGKAT PENDIDIKAN DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DALAM MELAPORKAN PAJAK RESTORAN DI KOTA PEKANBARU - Manalu, Derli; Nasir, Azwir; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Tax has an important role in Indonesia, considering the government’s national development requires relatively large funds. The taxation system in Indonesia are depending on how Tax payers are being active on fulfilling the obligation of taxation, the requiring a high compliance. This study aims to examine the effect awareness, tax penalties, education level, service of tax authorities against tax compliance. The population in this study is the individual taxpayers listed on DISPENDA at Pekanbaru. The sampling technique using convenience sampling method and determination of sample size in this study was calculated by using the formula of slovin obtained by 100 respondents. The data of this research is using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The results of this study show that awarness, tax penalties, service of tax authorities have effect on tax compliance with significant rate 58,9%. Viceversa education level has no effect regarding on tax compliance with significate.Keywords: Awareness, Penalties, Education, Service, and Compliance